2016
DOI: 10.1017/s003118201600024x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct courses of infection withLeishmania(L.)amazonensisare observed in BALB/c, BALB/c nude and C57BL/6 mice

Abstract: Leishmania (L.) amazonensis [L. (L.) amazonensis] is widely distributed in Brazil and its symptomatic infections usually lead to few localized lesions and sometimes to diffuse cutaneous form, with nodules throughout the body, anergy to parasite antigens and poor therapeutic response. The variability of these manifestations draws attention to the need for studies on the pathophysiology of infection by this species. In this study, we analysed the course and immunological aspects of L. (L.) amazonensis infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 41 publications
2
37
0
Order By: Relevance
“…amazonensis develop small lesions in C57BL/6 mice. In fact, LV79 lesions in this mouse strain increase until six weeks after inoculation and decrease thereafter, although parasites can still be found in lesions until thirteen weeks post infection [ 30 ]. On the other hand, PH8 strain was shown to generate lesions of increasing size in the same mouse strain [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…amazonensis develop small lesions in C57BL/6 mice. In fact, LV79 lesions in this mouse strain increase until six weeks after inoculation and decrease thereafter, although parasites can still be found in lesions until thirteen weeks post infection [ 30 ]. On the other hand, PH8 strain was shown to generate lesions of increasing size in the same mouse strain [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the infecting Leishmania species and host genetics, lesions progress into erythematous nodules, indurated plaques, scaly plaques, or ulcers ( Nylén and Eidsmo, 2012 ). The relationship between parasite growth, lesion formation, and immunity has been studied by several authors in different mouse strains ( Lira et al, 2000 ; Cardoso et al, 2010 ; Velasquez et al, 2016 ; Souza et al, 2018 ). Velasquez et al (2016) have shown that L. amazonensis -infected C57BL/6 mice developed smaller lesions that progressed to complete healing, while BALB/c and BALB/c nude mice developed progressive lesions, which correlated to the parasite load.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between parasite growth, lesion formation, and immunity has been studied by several authors in different mouse strains ( Lira et al, 2000 ; Cardoso et al, 2010 ; Velasquez et al, 2016 ; Souza et al, 2018 ). Velasquez et al (2016) have shown that L. amazonensis -infected C57BL/6 mice developed smaller lesions that progressed to complete healing, while BALB/c and BALB/c nude mice developed progressive lesions, which correlated to the parasite load. In the present study, a positive correlation between parasite load and lesion size was also found in C57BL/10 mice but not in C3H/He.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed that lesion development was independent of T/B cells in CL models using L. major [7] or Leishmania amazonensis [8]. Other studies showed that lesion development caused by L. major [9,10] or L. amazonensis [11] infection was delayed and less severe in the absence of T/B cells. Soong et al showed that CD4 + T lymphocytes are indispensable for pathogenesis during L. amazonensis infection [12].…”
Section: Introductionmentioning
confidence: 99%